Successful Management of Haemoglobinuria caused by Babesiosis in a Crossbred cow - K Karthika; S Yogeshpriya; Lakshmikantan A; Ajay P; Premalatha.N (Indian Journal of Veterinary Medicine, 2024)
A five year old pregnant cross-bred HF cow was reported with the history of anorexia, coffee coloured urine, absence of rumination for a period of three days. Congested conjunctival mucous membrane,  enlarged lymph nodes, elevated heart rate and pulse rate were noticed. On auscultation, heart sound was heard over extended area. Blood smear examination showed piroplasms in RBC. Haematological and serum biochemical analysis revealed anemia, hyperbilirubinemia and moderate elevation of BUN, AST and hypoproteinaemia. Diagnosis was made based on characteristic clinical signs, blood smear and haemato-biochemical alterations. Treatment with diminazene aceturate (@3.5mg/kg b.wt deep I.M) was given. Other treatment included oxytetracycline (@ 10 mg /kg b.wt I.V) along with supportives per os for 5 days. Animal recovered uneventfully.